Answer:
![6.03\cdot 10^(-12) m](https://img.qammunity.org/2020/formulas/physics/college/eao3t7bnrb6t5lokcfjue058vqv0milw42.png)
Step-by-step explanation:
First of all, we need to find the initial wavelength of the photon.
We know that its energy is
![E=301 keV = 4.82\cdot 10^(-14)J](https://img.qammunity.org/2020/formulas/physics/college/ershd0ij55q5dlp8w5jr7s782n8j8cpvt9.png)
So its wavelength is given by:
![\lambda = (hc)/(E)=((6.63\cdot 10^(-34) Js)(3\cdot 10^8 m/s))/(4.82\cdot 10^(-14) J)=4.13\cdot 10^(-12)m](https://img.qammunity.org/2020/formulas/physics/college/dm6ofpwv5d81b245l7h8cm2g06jb3wt7fk.png)
The formula for the Compton scattering is:
![\lambda' = \lambda +(h)/(mc)(1-cos \theta)](https://img.qammunity.org/2020/formulas/physics/college/tyzawanaai83zxiv5at5w4zfb4zonldhn7.png)
where
is the original wavelength
h is the Planck constant
m is the electron mass
c is the speed of light
is the angle of the scattered photon
Substituting, we find
![\lambda' = 4.13\cdot 10^(-12) m +(6.63\cdot 10^(-34) Js))/((9.11\cdot 10^(-31)kg)(3\cdot 10^8 m/s))(1-cos 77.5^(\circ))=6.03\cdot 10^(-12) m](https://img.qammunity.org/2020/formulas/physics/college/m6moas96vmsnlvezrcqpg3gwwztutakgvd.png)